To What Extent Can Community-based Playgroup Programmes Targeting Low-income Children Improve Learning Outcomes Prior to Entering the Reception Year in South Africa? A Quasi-experimental Field Study. Issue 1 (2nd January 2023) - Dawes, Andrew; Biersteker, Linda; Snelling, Matthew; Horler, Jessica; Girdwood, Elizabeth
ABSTRACT: Research Findings : Community-based playgroups in low-and-middle-income countries increase access to early learning at lower cost than centers. However, evidence of effectiveness is limited. The effects of one, two, or three playgroup sessions per week on children's performance on the Early Learning Outcome Measure (ELOM) ( n = 112; baseline M = 55.32 months) were investigated using a quasi-experimental design. Data on children's home learning environments was obtained from primary caregivers, and program staff provided information on playgroup characteristics. Multilevel modeling demonstrated significant differences between programs in ELOM score improvement over eight months participation ( F = 6.48; p = .01); Fisher LSD Post Hoc pairwise comparisons indicated that three session playgroups produced significantly greater gains than two and one session models ( p < .01). ELOM Total scores at baseline, and the quality of children's interactions with adults and peers, predicted growth in ELOM Total scores by endline. Baseline age, height-for-age, child-practitioner ratio, and caregiver time for activities with their children, predicted growth in certain ELOM domains at endline. Practice or Policy : Until provision of quality center-based provision is realized, our findings indicate that well-designed community-based playgroups of sufficient dose, have the potential to improve learning outcomes and school readiness in children from poor households.